Development of a Novel Rapid Immunodiagnostic Kit Based on Flagellar 40 kDa Antigen Epitope for the Detection of Typhoid Fever in Indian Patients. (5th February 2013) - Mitra, Rahul; Bhan, Surya; Nath, Gopal; Kumar, Narender; Ali, Ziledar
Abstract : To aid the clinical diagnosis of typhoid fever in India, where most hospitals and primary health centres have no facilities for culture, we report on the development of a novel and rapid immunodiagnostic kit for the direct detection of Salmonella Typhi—specific IgG antibodies against S . Typhi flagellar H antigen. The disease often does not show a specific clinical picture, and can be confused with other febrile illness such as malaria, dengue fever and Staphylococcus aureus . To overcome the problem of cross reactivity specific epitope of the flagellar H antigen was immobilised on the testing kit strip eliminating chances of cross reactivity and false positive results thereby increasing the specificity of the test. Since the immunodiagnostic kit, uses the flagellar H antigen from bacteria present in our country, the antibodies present in the serum of patients of our country will have maximum binding affinity, enhancing the sensitivity of our test kit. The immunodiagnostic kit on analysis gave a positive result with clinically diagnosed typhoid positive patient serum and negative results were obtained with the sera of clinically diagnosed malaria, abscess of Staphylococcus aureus and Visceral leishmaniasis (Kala-azar) patients.